2017
DOI: 10.1002/jor.23056
|View full text |Cite
|
Sign up to set email alerts
|

Expression of XBP1s in fibroblasts is critical for TiAl6V4 particle‐induced RANKL expression and osteolysis

Abstract: Wear particle-induced osteolysis is a major cause of aseptic loosening, which is one of the most common reasons for total hip arthroplasty (THA) failure. Previous studies have shown that the expression of Receptor activation of nuclear factor (NF)-kB (RANKL) by fibroblasts in periprosthetic membrane played a crucial role in wear particle-induced osteolysis. However, the underlying mechanism of RANKL expression remains largely unknown. In the present study, we investigated the effect of TiAl V particle (TiPs)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recently, increasing evidence has suggested that as a representative of host factors, single nucleotide variations (SNVs) were also linked to PTOM development. Such SNVs included but were not limited to rs689466 in cyclooxygenase-2 (COX-2) gene (Wang et al, 2017), rs16944, rs2234663, rs1143627, rs4251961, rs1800796, and rs2234663 in interleukin (IL) genes (Alves De Souza et al, 2017;Jiang et al, 2020). These findings demonstrated that SNVs might play essential roles in PTOM development.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, increasing evidence has suggested that as a representative of host factors, single nucleotide variations (SNVs) were also linked to PTOM development. Such SNVs included but were not limited to rs689466 in cyclooxygenase-2 (COX-2) gene (Wang et al, 2017), rs16944, rs2234663, rs1143627, rs4251961, rs1800796, and rs2234663 in interleukin (IL) genes (Alves De Souza et al, 2017;Jiang et al, 2020). These findings demonstrated that SNVs might play essential roles in PTOM development.…”
Section: Discussionmentioning
confidence: 97%
“…However, the ratio of revision after hip arthroplasty still remains at a high level with aseptic loosening accounting for the largest part of surgical failure. Wear particles are regarded as a critical role in the pathogenesis of aseptic loosening and osteolysis by interacting with multiple cell types from the peri-implant tissue and resulting in various biological reactions ( Wang et al., 2013 ; Wang et al., 2015a ; Wang et al., 2017a ). Most studies on particle-induced osteolysis have focused on the role of local factors in mediating bone resorption and bone formation ( Deng et al., 2017b ; Liu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2011) suggested that Bifidobacterium can protect from EPEC infection. In addition, our previous study suggested that L. casei could reduce particle-induced osteolysis by decreasing the M1-like macrophage/M2-like macrophage ratio ( Wang et al., 2017a ). Collectively, administration of probiotic, especially EPEC-fighting strains, in aseptic loosening patients may also be a potent treatment approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations